DEVELOPMENT OF E-COMMERCE MODELS AND ITS CURRENT CHALLENGES - Baran , R.Ya. (The actual problems of regional economy development, 2017)
The article investigates the development of E-commerce business models and highlights its current problems. The aim of the article is to research the application features of E-commerce models, forms and instruments, as well as to define its basic challenges at the present stage of world economic development. The article explores the current state of E-commerce market development both worldwide and in Ukraine. This allows determining the mainstream of E-commerce market - growth of M-commerce and transnational online trade. The article analyzes the activities of leading global marketplaces and offers their performance comparison. It defines the basic modifications in E-commerce models and singles out the key problems in this field thus enabling domestic enterprises to improve the efficiency of their Internet business activities.